GE_GERICHTE P/3239/2020 vom 12. März 2024 - GE Cour de justice (2024)
ABUS DE CONFIANCE;FAUX MATÉRIEL DANS LES TITRES;DIFFAMATION;PREUVE LIBÉRATOIRE;IN DUBIO PRO REO | CP.138.ch1; CP.173.ch2; CP.172.chter; CP.173.ch1; CP.251.ch1